Internal Mobility after the Expansion of the Welfare State: Evidence from Spain - Catalina Amuedo-Dorantes; Cristina Borra (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
The Spanish welfare state was practically inexistent in the 1980s. It expanded throughout the 1990s and became fully in place by the 2000s. At the same time, internal migration rates dropped to less than 0.3 percent -among the lowest in the world. In a country with large labor market imbalances, internal mobility can prove crucial to economic growth. We look at the role that non-contributory pensions might have played on inter-provincial mobility over the past two decades. We find that the expansion of the welfare state has curtailed the mobility of young working-age individuals, especially less educated women. The effects are unique to non-contributory pensions, and are not restricted to cohabitating family members or tied to the care for disabled relatives, signaling the need for policy measures that facilitate the mobility of the young from lower income households.
Keywords: I38; J61; R23; 330; internal migration; labor mobility; welfare benefits